PENGARUH PERSONAL SELLING TERHADAP KEPUTUSAN BERKUNJUNG DI JENDELA ALAM - Prasetyo, Adhitya Aji; Ridwanudin, Oce (THE Journal : Tourism and Hospitality Essentials Journal, 2016)
One of the areas in Indonesia which has many tourism potentials is West Java. It has so attracted many touristsfor its beauty in natural and cultural resources. Bandung is the capital of West Java. It has so many tourists'attractions. One of the tourist’s attractions is “Jendela Alam," the educational tourism destination thatcombines the idea of farm tourism activities and recreation park. Most of the visitors are students or schoolsthat want to study about farming activities. However, there are many competitors that offered the sameproducts and services right now, so the management has a big effort to anticipate the competitive situation.One of the efforts is by developing the personal selling activities to encourage schools for visiting the place.Thus, this research studied the personal selling as the independent variable that consists of some sub variables,namely, building relationship, closing the deal, and building loyalty. Furthermore, the dependent variable isthe visiting decision. The method of the research is descriptive and verification research. The researchinstrument is the questionnaires that are distributed to 100 respondents. The data were analysed multipleregressions statistical analysis. The result shows that there was a significant influence between the personalselling activities of the visit decision to this tourists' attraction.